Unlicensed Medicines in the UK - Legal Frameworks, Risks, and their Management. Issue 1 (2017) - Bourns, Ian M.
The UK laws regarding the licensing of medicines have been developed to reduce the likelihood of harm through their use. Unlicensed medicines lie outside that harm management process; they have additional risks and require professional responsibilities that are complex. Therefore, pharmacy practice applies risk management tactics that are specific to how it manages unlicensed medicines, especially in hospitals, where the risks of their use is at its highest. Due to increasing demand and costs - but static funding - healthcare in the UK's National Health Service is under stress and undergoing a period of transformation and cost savings. That transformation affects all areas of pharmacy practice and medicines procurement. Service leaders need to keep a focus on maintaining safety systems for unlicensed medicines through a period of change, including potential changes in roles and responsibilities.